Incidence and prevention of infective endocarditis and bacteraemia after transcatheter aortic valve implantation in a French university hospital: a retrospective study. Issue 1 (May 2018) - Gallouche, M.; Barone-Rochette, G.; Pavese, P.; Bertrand, B.; Vanzetto, G.; Bouvaist, H.; Pierre, I.; Schmitt, D.; Fauconnier, J.; Caspar, Y.; Recule, C.; Picot-Guéraud, R.; et al.
Summary: Infective endocarditis (IE) after transcatheter aortic valve implantation (TAVI) is a rare but severe complication. Among 326 patients who underwent TAVI at Grenoble Alpes University Hospital, six (1.8%) cases of IE and 11 (3.4%) cases of bacteraemia were identified. No cases of IE were linked to the intervention; one was due to Staphylococcus aureus despite a screening and targeted decolonization strategy. This underscores the need for randomized studies to evaluate the benefit and cost-effectiveness of this policy.